PENGARUH PENGALAMAN KERJA, DISPILIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN CV. PERSADA PRATAMA - I Gst A Ira Cristin Wihelmina; I Nengah Sudja; Ida Bagus Made Widiadnya (VALUES, 2023)
Human resources as the main element in an institution have a very big role in achieving the goals that have been set. A company or organization in carrying out its activities requires human resources who have capacity in a field. Therefore human resource management is the most important thing to be done by a company or organization. Human Resource Management is one of the efforts made by companies to manage their human resources. These resources are directed to achieve predetermined company goals. One of them is by paying attention to work experience, work discipline and motivation. By paying attention to work experience, work discipline and motivation are expected to be able to influence employee performance in a better direction. This study aims to determine the effect of work experience, work discipline and work motivation on the performance of CV employees. Persada Primary. This research was conducted at CV. Persada Pratama with a total sample of 42 employees as research respondents. The method of determining the sample in this study is the census method. Data collection was carried out through documentation, interviews and questionnaires. The data analysis technique used in this study was SPSS version 26 for windows. Based on the results of the analysis, this study shows that work experience has a positive and significant effect on employee performance at CV. Persada Primary. This means that the better the work experience provided by the organization, the better the performance of employees. Work discipline has a positive and significant effect on employee performance at CV. Persada Primary. This means that the more disciplined employees will improve their performance. Work motivation has a positive and significant effect on positive and significant employee performance at CV. Persada Primary. This means that the motivation provided by the company will encourage employees to be able to improve their performance.